2020
DOI: 10.1038/s41370-019-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of housing interventions on indoor air quality and energy consumption using coupled simulation models

Abstract: While residential energy and ventilation standards aim to improve the energy performance and indoor air quality (IAQ) of homes, their combined impact across diverse residential activities and housing environments has not been well-established. This study demonstrates the insights that a recently-developed, freely-available coupled IAQ-energy modeling platform can provide regarding the energy and IAQ trade-offs of weatherization (i.e., sealing and insulation) and ventilation retrofits in multifamily housing acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…To calculate the efficiency of a built school campus in London, Jain et al [3] considered the interrelationships between energy and indoor air environment, and they concluded that building performance depends on two important parameters, energy, and indoor air quality (IAQ) perspective [3]. Underhill et al [4] evaluated a coupled model of energy and indoor air quality using the co-simulation method, and the conclusion of this integrated model has high accuracy in calculating both energy and indoor air quality parameters [4]. Energy, thermal comfort, and indoor air quality performance for underground buildings were evaluated by Yu et al [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the efficiency of a built school campus in London, Jain et al [3] considered the interrelationships between energy and indoor air environment, and they concluded that building performance depends on two important parameters, energy, and indoor air quality (IAQ) perspective [3]. Underhill et al [4] evaluated a coupled model of energy and indoor air quality using the co-simulation method, and the conclusion of this integrated model has high accuracy in calculating both energy and indoor air quality parameters [4]. Energy, thermal comfort, and indoor air quality performance for underground buildings were evaluated by Yu et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…This type of buffering material can adsorb or desorb moisture and VOCs from ambient air can maintain its value in the appropriate levels of moisture and indoor air quality performances [17]. Many recent studies have been performed to exploit the combination of EnergyPlus and CONTAM models that the results of this coupling are more accurately compared to single models [4]. WUFI models with CONTAM have been used to increase the accuracy of assessing performances of indoor air quality and moisture [18].…”
Section: Introductionmentioning
confidence: 99%
“…World energy consumption is rising rapidly as a result of the increasing demand for energy from emerging and developed economies associated with various sectors, including the building sector. 1,2 More than half of energy usage portion in buildings comes from mechanical systems of heating, ventilation and air-conditioning (HVAC) to achieve better indoor air quality (IAQ) and thermal comfort, which leads to high energy cost. This is directly contributing to the global warming phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the indoor environment has been increasingly recognized for its relevance to human health and well-being [ 11 ]. Prior studies on the effects of residential ventilation on indoor exposure has led to a continued concern about the impact of weatherization on human health [ 12 18 ]. The World Health Organization (WHO) established a set of 12 housing inadequacies that had sufficient evidence for estimating disease burden [ 19 ].…”
Section: Introductionmentioning
confidence: 99%